EFL Students’ Attitudes towards the Use of Podcasts as a Language Learning Medium to Increase Learning Interest - Aprianto, Dedi (SALEE: Study of Applied Linguistics and English Education, 2024)
The study on the use of podcast as a technology-mediated method or medium to increase EFL students’ interest is still limited. Generally, some studies focus more on the effects of using podcast on students’ listening and speaking skills. The present study aimed at examining the effect of podcast in English language learning towardss EFL students’ interest by analyzing their attitudes to podcast. The study was carried out using a quantitative method by employing a cross-sectional survey. Data collection was employed through a questionnaire. The data was analyzed by using a descriptive statistics to measure the frequency percentages. The results indicated that the tertiary students’ showed a very positive attitude towardss the use of podcast to influence EFL students’ interest. Four findings were suggested, namely the willingness of using podcast, courage to encourage EFL learning engagements and language proficiency, podcasts as appropriate and fun learning media providing varied materials, and podcast as a the portable, open-accessed and efficient medium. The findings of the present study are significant to present the Info-Tech-based alternative language learning media and sources or as complementary resources and the innovative and interesting sources can motivate to engage more. Podcasts  is the complementary medium and authentic materials for empowering English engagements and increasing interest.